PSYCHOLINGUISTIC CONFLICTS IN THE SPEECH OF LITERARY CHARACTERS IN FRENCH LITERATURE - Abdullayeva Mohichexra Umrzoq qizi; Radjabov Ruslan Rajabmurodovich (Western European Studies, 2026)
This article explores psycholinguistic conflicts manifested in the speech of literary characters in French literature. The study focuses on the discrepancy between internal psychological states and external verbal expression, as well as the linguistic representation of unconscious processes and social constraints. Drawing on selected works by Gustave Flaubert, Albert Camus, Marcel Proust, and Jean-Paul Sartre, the paper applies qualitative discourse analysis and psycholinguistic interpretation to literary texts. The findings demonstrate that characters’ speech functions not only as a means of communication but also as a reflection of inner conflicts, emotional alienation, and identity fragmentation. The study highlights the relevance of psycholinguistic approaches for literary analysis and contributes to interdisciplinary research at the intersection of linguistics, psychology, and literary studies
Keywords: literary discourse; psycholinguistics; inner speech